2019
DOI: 10.1037/int0000148
|View full text |Cite
|
Sign up to set email alerts
|

Exploring innovative moments in a brief integrative psychotherapy case study.

Abstract: The present study examined the emergence of innovative moments in a successful case of Brief Integrative Psychotherapy (BIP) based on Hill’s 3-stage model. Hill’s model suggests that optimally therapeutic processes involve exploration (based on client-centered therapy), insight (based on psychoanalytic therapy), and action (based on behavioral therapy). Innovative moments are exceptions to the problematic pattern of meaning that brought the client to therapy. Previous studies showed that their occurrences in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Replicating previous results with a case study (Nasim et al, 2018), our study showed significant relations between IMs and three out of four session impact dimensions on the client. According to Stiles and colleagues (1994), the clients’ internal reactions that are captured by the SEQ ratings indicate the interpersonal climate, sense of progress, and consumer satisfaction of the session.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Replicating previous results with a case study (Nasim et al, 2018), our study showed significant relations between IMs and three out of four session impact dimensions on the client. According to Stiles and colleagues (1994), the clients’ internal reactions that are captured by the SEQ ratings indicate the interpersonal climate, sense of progress, and consumer satisfaction of the session.…”
Section: Discussionsupporting
confidence: 85%
“…This exploratory study was the first to identify and explore IMs in eight cases of BIP with clients seeking help for a wide range of psychological problems, thereby widening the scope of a case study design drawn from the same database (Nasim et al, 2018). Our results showed that IMs could be reliably identified in BIP and that their proportion increased while symptomatic measurements decreased along treatments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Esposito, Ribeiro, Alves, Gonçalves, & Freda, ) which are setting a new ground for a coding manual for groups. Likewise, replication efforts are being made with bigger samples and different therapeutic models such as Barlow's UP (ongoing study) and psychodynamic therapy (Nasim et al, ).…”
Section: Resultsmentioning
confidence: 99%